A catalog of Athericidae (Diptera) from Neotropical and Andean Regions - González, Christian R; Elgueta, Mario; Coscarón, Sixto (Zootaxa, 2019)
A catalog of the Athericidae from Neotropical and Andean Regions is provided. All valid names and synonyms are presented, totaling twenty-seven species and three genera in these Regions. All references known from the taxonomic and biological literature are given, including information about name, author, year of publication, page number, type species, type locality and bibliography. The genus Atherix Meigen is not represented in Neotropical nor Andean Regions.